TABOO AND EUPHEMISMS IN BATAK TOBA CULTURE - Simangunsong, Reka; Lubis, Tasnim; Zein, T. Thyrhaya (TALENTA, 2021)
Even though both are prohibitions, the terms taboo and taboo are two different things. Taboo causes violators to be plagued, while taboo only causes physical sanctions or social sanctions. To avoid violating the pronunciation of taboo words, substituting words or sentences that are considered taboo is carried out. Suppose spoken in a context to change the connotation of the consequences of the mention (euphemism). This study focuses on finding out what taboos and euphemisms are in the Toba Batak culture. The method used in this research is descriptive qualitative by using observation and interview techniques. The study results found that there were five types of taboos and euphemisms found in the Toba Batak culture. First, taboos and euphemisms on gender boru-boru > ito (woman), ripe > parnijabu (wife). Second, taboos and euphemisms are related to body parts mapampang > hahurangan dipamatang (disabled). Third, taboos and euphemisms related to death (mate > monding (death). Fourth, taboos and euphemisms are related to philosophy, religion or customs, such as the taboo on marrying a clan.